Verses of Wishing in the Holy Quran - Seif El-Din Hadi Hamad; Hemin Aziz Brime (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
There is no doubt that the Noble Qur’an is the book of guidance to the path of righteousness to ensure a secure and reassuring life, and that God Almighty has guided Muslims in it to the most complete guidance and guided them with His knowledge and wisdom, the Most High, the best evidenc . For among the non-Muslims there are those who have sympathy and resentment as long as Muslims do not find out about them, if God Almighty does not account for them in His Mighty Book and in numerous verses, where He warned the believers against them. These verses are of great importance for guiding Muslims and their policies towards others in all times and places. They have important implications as they revolve around basic issues related to their doctrinal and cultural life, their subjective and entity existence, and their administrative and self-independence. Verses that reveal their enemies the veil about what they would like from the hardship and betrayal of Muslims under their hands, and the invalidation of their beliefs and religion, which God has honored them with.